Studi Komparasi Kinerja dari Adaptive Routing Protocol OSPFv3, RIPng, EIGRP IPv6, dan IS-IS pada Jaringan IPv6 - Reynaldi Firman Tersianto; Nurul Hidayat; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Routers on both IPv4 and IPv6 networks require routing protocols, so that routers can search for the best route used to transmit data packets from the transmitting node to the receiving node. Based on the characteristics, routing protocols are classified into adaptive / dynamic routing and static routing. Adaptive routing is a routing protocol that chooses routes for transmitting data packets based on conditions on the network. Because each adaptive routing protocol has different algorithms in determining the best route, it is necessary to compare the performance of the adaptive routing protocol in order to obtain the best performance of the adaptive routing protocol. This research was conducted to compare the best performance of the adaptive routing protocol OSPFv3, RIPng, EIGRP IPv6, and IS-IS IPv6 by using the Graphical Network Simulator-3 (GNS3) network emulator. The configuration of the adaptive routing protocol is implemented in a mesh network topology. ICMP ping packet command is used in this research because the number of packets that failed and successfully sent and the average value of round-trip time (RTT) can be known. This is needed because the best adaptive routing protocol performance is one that has a smaller amount of packet loss and faster convergence time and an average RTT. The results of this research indicate that OSPFv3 and IS-IS IPv6 have the best performance based on the amount of packet loss smaller and faster convergence time. Based on the faster average RTT, IS-IS IPv6 has the best performance compared to other adaptive routing protocols.